The Effect of the Use of Problem Based Learning (PBL) Based on Student Worksheets (LKPD) on the Mastery of Science Concepts in Class V Ecosystem Materials - Dewi Suhandary; Atikah Syamsi; Heru Mudiyanto (UIN Siber Syekh Nurjati Cirebon, 2024)
The background of this research is that there is no influence on the use of teaching materials in accordance with curriculum provisions, target characteristics, and problem solving demands and the application of the Problem Based Learning (PBL) model provided by teachers in learning has not been fully listed to increase students' understanding. The purpose of this study was to determine the effect of Problem Based Learning (PBL) student worksheets on Ecosystem Component Material by utilizing scientific literacy on ecosystem material (water cycle) at SDN Cipedak 05 Pagi, South Jakarta. The research method used is the experimental method with the approach used in this study is a quantitative approach. The form of the design is